2018
DOI: 10.1371/journal.pone.0197089
|View full text |Cite
|
Sign up to set email alerts
|

Clonal plasticity and diversity facilitates the adaptation of Rhododendron aureum Georgi to alpine environment

Abstract: Four small oval populations and five large intensive populations of Rhododendron aureum growing at the alpine in Changbai Mountain (China) were studied in two types of habitat (in the tundra and in Betula ermanii forest). Identification and delimitation of genets were inferred from excavation in small populations and from amplified fragment length polymorphism (AFLP) markers by the standardized sampling design in large populations. Clonal architecture and clonal diversity were then estimated. For the four smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
(53 reference statements)
3
11
0
Order By: Relevance
“…The surface soil water content of inland river wetlands is relatively lacking, so the roots of clonal plants are mainly distributed in deep soil layers for absorbing middle and deep layer soil water [77]. The study results on soil water response of the clonal modules for Spartina alterniflora and Duchesnea indica were consistent with those of our results [68,75].…”
Section: Spatial Expansion Driving Forces Of Clonal Modules For Phragsupporting
confidence: 89%
See 1 more Smart Citation
“…The surface soil water content of inland river wetlands is relatively lacking, so the roots of clonal plants are mainly distributed in deep soil layers for absorbing middle and deep layer soil water [77]. The study results on soil water response of the clonal modules for Spartina alterniflora and Duchesnea indica were consistent with those of our results [68,75].…”
Section: Spatial Expansion Driving Forces Of Clonal Modules For Phragsupporting
confidence: 89%
“…Therefore, the increasing integration effects among clone network of Phragmites australis with increasing heterogeneity. Other results for the clonal plants of Leymus chinensis and Duchesnea indica had similar conclusions with the same growth trends of the rhizome internode length, spacer length, and branch angle, and the reciprocal relationship between branch intensity and spacer length and ramet number [75][76]. These results showed that clonal plants could directly adjust their morphological plasticity and biomass distribution patterns in order to survive in environmental heterogeneity.…”
Section: Spatial Expansion Strategies Of Clonal Modules For Phragmitesupporting
confidence: 69%
“…Population codes according to Table 1 Table 3 Mean value of relatedness estimator (R), contributions of unrelated individuals (U), half-siblings (HS), full-siblings (FS) and parent offspring specimens (PO) and results of the Mantel tests (r) comparing genetic and geographic distance matrices in the B. humilis populations. Population codes according to allowing for this plant to colonise and exploit tundra and birch forest in Changbai Mountain in China (Wang et al 2018). In general, the predominance of some B. humilis clones can imply their selective advantage over othergenets; however, there is still a substantial overall clonal diversity in all populations analysed.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of clonal reproduction tends to increase with elevation [145,146] and aridity [147] as costs of sexual reproduction increase. Vegetative reproduction is often a plastic response to environmental conditions [145].…”
Section: Mating System Variationmentioning
confidence: 99%
“…Vegetative reproduction is often a plastic response to environmental conditions [145]. Vegetative ramets can forage for resources or optimal conditions in pioneer communities or at range edges, enabling acclimation to novel or stressful conditions under climate change [146][147][148]. Asexual reproduction and clonal growth could become more prevalent in habitats disturbed by climate change.…”
Section: Mating System Variationmentioning
confidence: 99%